Self-Employment Can Be Good for Your Health - Milena Nikolova (Global Labor Organization (GLO), 2018)
Drawing upon theoretical insights from the Job Demand-Control model, which links occupational characteristics to health, this paper provides the first causal evidence of the physical and mental health consequences of self-employment. Specifically, I utilize German longitudinal data for the period 2002-2014 and difference-in-differences estimations and find that both switches from unemployment to self-employment (necessity entrepreneurship) and transitions from regular employment to self-employment (opportunity entrepreneurship) lead to health enhancements for entrepreneurs with and without employees. Specifically, necessity entrepreneurs experience improvements in mental but not physical health, while opportunity entrepreneurship is associated with both physical and mental health gains, which is in line with the theoretical predictions. Importantly, the health improvements cannot be explained by changes in income or working conditions and are not driven by personality and risk preferences or the local unemployment conditions. The results have implications for entrepreneurship theory and practice, current and would-be entrepreneurs as well as policy-makers.
Keywords: I10; J01; L26; 330; mental health; physical health; self-employment; difference-in-differences